2021
DOI: 10.29359/bjhpa.13.3.04
|View full text |Cite
|
Sign up to set email alerts
|

The relatıonship between shooting performance and respiratory muscle strength in archers aged 9-12

Abstract: Introduction: The aim of this study is to investigate the relationship between shooting performance and pulmonary functions and respiratory muscle strength in archers. Material and methods: The research was conducted with 31 boy and 11 girl archers aged 9-12. The forced vital capacity (FVC), forced expiration volume in one second (FEV1), FEV1/FVC, peak expiratory flow (PEF), maximum voluntary ventilation (MVV), maximum inspiratory pressure (MIP), and maximum expiratory pressure (MEP) of the archers were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…MEP values are greater in boys than in girls. The same was found for children who are engaged in sports activities(Bostanci et al, 2021). This phenomenon is explained by an increased capability for male muscles to generate maximum power output.…”
supporting
confidence: 58%
“…MEP values are greater in boys than in girls. The same was found for children who are engaged in sports activities(Bostanci et al, 2021). This phenomenon is explained by an increased capability for male muscles to generate maximum power output.…”
supporting
confidence: 58%
“…The experimental group performed additional inspiratory muscle training for eight weeks with a commercially available respiratory muscle trainer [31]. Bostanci et al [32] revealed no significant difference between the male (307.32±43.92) and females (304.91±44.81) for peak expiratory flow among athletes.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, another possible explanation for the relationship between pulmonary functions and shooting performance may be due to the fact that pulmonary capacity can affect breathholding time. Some previous studies demonstrate links between shooting performance and lung capacities in archers [98,99]. However, another study showed no correlation between air pistol shooting performance and pulmonary function in shooters competing in the young female category (age 16) [12].…”
Section: Discussionmentioning
confidence: 99%